Developing the I am Anti-Corruption Learning Model and Its Impact on Reducing Student Fraud - Alhamuddin Alhamuddin; Dinar Nur Inten; Rabiatul Adwiyah; Nizar Fauzan (Jurnal Pendidikan Progresif, 2024)
Developing the I am Anti-Corruption Learning Model and Its Impact on Reducing Student Fraud. Objective; this study is to develop the 2A (I am Anti-Corruption) learning model, aimed at integrating anti-corruption concepts and their impact on reducing academic fraud. Method; This research is a type of development using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation).  The research was conducted at PGII 2 Bandung Senior High School. Data collection was done through observation and in-depth interviews on anti-corruption values and student assignments. and questionnaires on anti-corruption values. Data analysis used qualitative and quantitative approaches. Findings; The results showed that the Anti-Corruption Learning Model and its impact on the reduction of student fraud, the R-squared value of 0.349. The R-squared value indicates that although there is a relationship between the anti-corruption learning model and reducing student fraud, there are other factors or variables outside the model that influence or contribute to reducing student fraud. These unaccounted-for factors may include socio-economic conditions, cultural aspects, enforcement mechanisms, individual attitudes or other interventions that may affect fraud reduction. Conclusion; Anti-corruption education is a lifelong process. It needs to be instilled in children as early as possible Keywords: anti-corruption, learning, I'm anti-corruption, student fraud, academic fraud.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202452